Aktualisasi Syariah dan Fikih dalam Menyelesaikan Berbagai Persoalan Hukum - Abdul Wahab Abd Muhaimin (Universitas Islam Negeri Jakarta, 2015)
In line with the dynamics of society and the advancement of science, various contemporary legal issues occur. This issues need solution from Islamic law. This study indicated that Islam law still based on Al-Quran and Hadith and it still relevan tgroughout the ages, and it will always correspond to the society and technology. It convenients with the rule: “Islam is appropriate and relevant to every condition, state, time, and place”.DOI: 10.15408/ajis.v15i2.2868